Changes in proportional mortality from diabetes and circulatory disease in Mauritius and Fiji: possible effects of coding and certification - Stephen Morrell; Richard Taylor; Devina Nand; Chalapati Rao (BMC, 2019)
Abstract Background Many developing countries are experiencing the epidemiological transition, with the majority of deaths attributed to cardiovascular disease, cancer, Type 2 diabetes (T2DM) and others. In some countries, large proportional mortality attributed to diabetes is evident in official mortality statistics, with Mauritius and Fiji rated as the highest in the world. Methods This study investigates trends in recorded diabetes and cardiovascular disease mortality in Mauritius and Fiji under coding from the International Classification of Diseases (ICD) versions 9 and 10, using mortality data reported from these countries to the World Health Organization (WHO). Results In Mauritius over 1981-2004, T2DM proportional mortality varied between 4% and 7% in males (M) and 5% and 9% in females (F). In 2005 there was a sudden increase to M 20% and F 25%, which continued to M 25% and F 30% by 2012. Over 1981-2004 the proportion of circulatory disease mortality rose from 44% to 49% in males, and from 46% to 57% in females. In 2005, circulatory disease mortality proportions fell precipitously to 34% in males and 37% in females, and declined to 31% and 34% by 2013. ICD-10 coding was introduced in 2005. In Fiji, sharp rises in proportional T2DM mortality from 3% in both sexes in 2001 to M 15% and F 20% in 2002 were followed by more gradual trend increases to M 20% and F 26% by 2012-13. Circulatory disease proportions fell steeply from M 57% and F 53% in 2001 to M 44% and M 38% by 2004, with subsequent less steep declines to M 39% and F 30% by 2012. ICD-10 coding was introduced in 2001. Conclusions Large, abrupt changes in diabetes and circulatory disease proportional mortality in Fiji and Mauritius coincided with the local introduction of ICD-10 coding in different years. There is also evidence for diabetes-related misclassification of underlying cause of death in Australia and the USA. These artefacts can undermine accurate monitoring of cause of death for evaluation of effectiveness of prevention and control, especially of circulatory disease mortality which is demonstrably reversible in populations.